LRP5-Mediated Lipid Uptake Modulates Osteogenic Differentiation of Bone Marrow Mesenchymal Stromal Cells - Lin, Jiachen; Zheng, Zhifa; Liu, Jieying; Yang, Guihua; Leng, Ling; Wang, Hai; Qiu, Guixing; Wu, Zhihong (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow mesenchymal stromal cells (BMSCs) harbor a subpopulation of skeletal progenitors with potency to undergo osteogenesis and are considered as favorable seeding cells in regenerative medicine. The past decade has witnessed tremendous advances in the understanding of the biological functions and regulations of BMSCs. Most recently, lipids, serving as important fuel sources in bone, were identified as critical modulators to determine the specification of skeletal progenitor cells during fracture healing and bone homeostasis. However, the regulatory role of lipids in the osteogenic differentiation of BMSCs has not yet been elucidated. In the present study, we investigated the implications of lipid availability in the osteogenic differentiation of BMSCs and firstly propose that lipid scarcity suppresses osteogenic differentiation of BMSCs as well as Wnt/beta-catenin signaling. We also identified the specific role of low-density lipoprotein receptor-related protein 5 (LRP5), a well-known Wnt/beta-catenin signal transducer, in modulating lipid uptake process of BMSCs during osteogenesis in vivo and in vitro. Notably, genes and molecules in Wnt-LRP5 signaling have been proved to involve in human diseases including osteoporosis and cardiometabolic disorders, and considered as therapeutic targets in drug discovery. With these evident data, we believe our findings will facilitate future development of pharmacological intervention, regenerative engineering and medical translation in bone and metabolic diseases.